Portable wrapping machine / Muhammad Hakim Hisam and Miqdad Khairulmaini - Hisam, Muhammad Hakim; Khairulmaini, Miqdad (School of Mechanical Engineering, 2023)
The lack of well-established portable wrapping machines in the market has led to a need for innovation in this field. Due to the limited availability of portable wrapping machines and their lack of features for easy operation and user-friendliness, this project aims to increase the production rate for small home businesses by presenting an improvised portable wrapping machine to ease the wrapping process. The product design incorporates the installation of a motor to wrap small cylinders or boxes within the machine's size. A power supply is used to convert AC current to DC current to supply electricity to the motor. The outcome of this project is a portable wrapping machine that is easy to operate, user-friendly, and capable of increasing production rates for small home businesses. This improvised portable bubble wrapping machine has the potential for commercial success as it provides an efficient solution to small home businesses by potentially increasing revenue for their businesses